2019
DOI: 10.1371/journal.ppat.1007813
|View full text |Cite
|
Sign up to set email alerts
|

A bacterial secreted translocator hijacks riboregulators to control type III secretion in response to host cell contact

Abstract: Numerous Gram-negative pathogens use a Type III Secretion System (T3SS) to promote virulence by injecting effector proteins into targeted host cells, which subvert host cell processes. Expression of T3SS and the effectors is triggered upon host cell contact, but the underlying mechanism is poorly understood. Here, we report a novel strategy of Yersinia pseudotuberculosis in which this pathogen uses a secreted T3SS translocator protein (YopD) to control global RNA regulators. Secretion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(59 citation statements)
references
References 79 publications
3
46
0
Order By: Relevance
“…Therefore, it is possible that some of the YopE detected in the supernatant of the Apo-IscR strain is a result of lysis rather than type III secretion. However, the 5-fold greater YopE levels in the cell pellet of the Apo-IscR mutant compared to WT (Fig 6) corroborates the hypothesis that this mutant is undergoing type III secretion, as active secretion feeds back on T3SS gene transcript levels through a positive feedback loop [31]. These results demonstrate that increasing IscR levels is sufficient to activate T3SS expression under anaerobic conditions.…”
Section: Ectopic Induction Of Iscr Under Anaerobic Conditions Is Suffsupporting
confidence: 73%
See 1 more Smart Citation
“…Therefore, it is possible that some of the YopE detected in the supernatant of the Apo-IscR strain is a result of lysis rather than type III secretion. However, the 5-fold greater YopE levels in the cell pellet of the Apo-IscR mutant compared to WT (Fig 6) corroborates the hypothesis that this mutant is undergoing type III secretion, as active secretion feeds back on T3SS gene transcript levels through a positive feedback loop [31]. These results demonstrate that increasing IscR levels is sufficient to activate T3SS expression under anaerobic conditions.…”
Section: Ectopic Induction Of Iscr Under Anaerobic Conditions Is Suffsupporting
confidence: 73%
“…While T3SS gene expression was detected within the entire splenic microcolony, enhanced expression was detected in bacteria localized at the microcolony periphery, i.e.-those bacteria in contact with host cells. It is possible that this T3SS expression in the microcolony periphery reflects host cell contact-dependent increase in type III secretion, leading to stabilization of lcrF and other T3SS genes [31]. This contact-dependent increase in T3SS gene expression is then an additional layer of regulation once IscR levels are high enough in deeper tissues to induce sufficient lcrF mRNA production.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, VirD2 may have enzymatic functions both within the bacterium and in the host plant cell. A recent study also indicated that Yersinia pseudotuberculosis uses the secreted T3SS translocator YopD to control RNA regulators and increase the abundance of LcrF, a common transcriptional activator of other T3SS effector genes 12 . N-linked protein glycosylation on arginine has also been reported for the EarP glycosyltransferase from E. coli and Pseudomonas aeruginosa 13 .…”
mentioning
confidence: 99%
“…Moreover, a consistently high degree of correlation between yscWp promoter activity and levels of secreted Yops was observed (Figs 4 and 5). This is impressive considering the complexity of transcriptional and post-transcriptional control of the yscWp transcriptional unit [51][52][53]. This represents compelling evidence for CpxR/RscB regulatory interplay in Ysc-Yop T3SS control, despite indications that active CpxR~P may not directly bind to rscB regulatory region ( Figs S3 and S4).…”
Section: Zinc-activated Rcsb Expression Is Subdued By Active Cpxrmentioning
confidence: 87%